1996
DOI: 10.1017/s1355617700001004
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of implicit and explicit knowledge in a case of psychogenic retrograde amnesia

Abstract: There have been few studies of psychogenic amnesia based on a cognitive or neuropsychological framework. In the present study, a patient with acute onset of profound psychogenic retrograde amnesia was examined. Although her performance on neuropsychological tasks revealed intact anterograde memory, language functioning, visuospatial and constructional skills, and mental speed and flexibility, she displayed severe impairments on a variety of retrograde memory tasks. Furthermore, initial observations revealed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
4
14
0
1
Order By: Relevance
“…The neuropsychological ¢ndings for our ten FRA patients agree generally with the ¢ndings of four other patients who have been tested for anterograde and retrograde amnesia during FRA (Campodonico & Rediess 1996; patient K of Treadway et al 1992;Kopelman et al 1994;Schacter et al 1982) and with the ¢ndings of three other patients who may have had FRA (the patient reported by De Renzi et al 1995; patient F of Treadway et al 1992; case M.M. of Lucchelli et al 1995).…”
Section: (A) Neuropsychological ¢Ndingssupporting
confidence: 86%
“…The neuropsychological ¢ndings for our ten FRA patients agree generally with the ¢ndings of four other patients who have been tested for anterograde and retrograde amnesia during FRA (Campodonico & Rediess 1996; patient K of Treadway et al 1992;Kopelman et al 1994;Schacter et al 1982) and with the ¢ndings of three other patients who may have had FRA (the patient reported by De Renzi et al 1995; patient F of Treadway et al 1992; case M.M. of Lucchelli et al 1995).…”
Section: (A) Neuropsychological ¢Ndingssupporting
confidence: 86%
“…All patients manifested impaired performance on attention and concentration tasks, which ranged from mild to severe. Consistent with our observations, attention deficits have been documented in previous studies of patients with psychogenic (dissociative) or functional amnesias Stracciari, Ghidoni, Guarino, Poletti, & Pazzaglia, 1994;Campodonico & Rediess, 1996). All patients in the present study demonstrated significant retrograde impairments of autobiographical-episodic memory and two showed additional significant impairments of retrograde semantic memory.…”
Section: Resultssupporting
confidence: 93%
“…First, in contrast to what was reported in the early clinical studies, many of the patients who were studied with neuropsychological testing did not recover from their condition, even after one or two years (e.g., Campodonico and Rediess 1996;Markowitsch et al 1997). Second, the findings across patients were variable.…”
mentioning
confidence: 79%
“…Specifically, one finds good anterograde memory function and significant retrograde amnesia, usually including an inability to recall one's name (see, e.g., Schacter et al 1982; patient K of Treadway et al 1992;Kopelman et al1994;Barbarotto et al 1996;Campodonico and Rediess 1996;Markowitsch et al 1997). In other case reports, an unequivocal diagnosis was not reached, but the findings were similar to what we have described here, and we believe it likely that these other patients also had functional amnesia (e.g., De Renzi et al 1995Renzi et al , 1997patient MM of Lucchelli et al 1995;Dalla Barba et al 1997;Papagno 1998;MackenzieRoss 2000;Nakamura et al 2002).…”
Section: Discussionmentioning
confidence: 99%